2019
DOI: 10.18549/pharmpract.2019.2.1438
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Lebanese pharmacists towards online and live continuing education sessions

Abstract: Background: Continuing education (CE) is an internationally recommended approach as a lifelong learning model for pharmacists, enabling them to maintain the necessary knowledge, skills and ethical attitudes so as to remain current and competent in their practice. Objectives: The objective of this study is to 1) describe factors associated with taking different types of CE courses among pharmacists in Lebanon, and 2) assess the correlation between types of CE activity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…The pilot study revealed no need for modification; its results were thus included in the study. Further methodological details are available in another publication 18. Statistical analyses were performed using SPSS version 23 (IBM SPSS Software, Chicago, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The pilot study revealed no need for modification; its results were thus included in the study. Further methodological details are available in another publication 18. Statistical analyses were performed using SPSS version 23 (IBM SPSS Software, Chicago, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
“…An online software was used to randomly select the community pharmacies sample using the list of pharmacies provided by the Lebanese Order of Pharmacists (OPL). Similar methodology was used in previous papers [22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: General Study Designmentioning
confidence: 94%
“…Retrieved studies were from the United States (n=9), [17][18][19][20][21][22][23][24][25] Australia (n=5), [26][27][28][29][30] United Kingdom (n=5), [31][32][33][34][35] Canada (n=3), [36][37][38] Lebanon (n=2), 39,40 Belgium (n=2), 41,42 Ethiopia (n=1), 43 Spain (n=1), 44 Malaysia (n=1), 45 United Arab Emirates (n=1), 46 Qatar (n=1), 15 and Egypt (n=1). 47 A summary of the included articles can be found in table 1.…”
Section: Resultsmentioning
confidence: 99%
“…37 Timing of a CE/CPD activity was shown to be an important factor that would encourage pharmacists to attend an activity. 28,40,44,45,47 As pharmacists in different countries may have slightly different duty schedules, CE/CPD activities need to be planned in a flexible manner to fit within their busy daily schedules.…”
Section: Factor 2: Access To Needs-based Educationmentioning
confidence: 99%